Diversity and inclusion in higher education : emerging perspectives on institutional transformation - Smith, Daryl G. (London : Routledge, 2014)
'In addition to many other issues that touch higher education around the world, diversity and equity in higher education is fast becoming a major opportunity and challenge to institutions, countries and regions. The increasing centrality of diversity is fueled in part by changing demographics, immigration, social movements, calls for remedies to historic grievances, and, the relationship between identity and access to power. This book will provide an opportunity to look at efforts at institutional change with respect to diversity in several countries where issues of diversity are moving beyond simply access for diverse populations to efforts at institutional transformation. Its purpose is to provide a comparative perspective with the hope that we will be able to see patterns across these contexts from which we might learn. Amongst other subjects it will address:The historic and contemporary context for diversity established and emerging salient identities how diversity is framed at a national and institutional level the prevailing strategies and policies for engaging diversity, again at the national and institutional level the role of special purpose institutions this critical book is an essential for higher education scholars and practitioners with background in higher education'--
Includes bibliographical references and index.
Keywords: Minorities -- Education (Higher).; Multicultural education; Inclusive education; Educational equalization